Environmental Psychology in Brazil: bibliometric study of scientific production in open access - Raquel Farias Diniz; José de Queiroz Pinheiro; Juliana Bezerra Moisés; Victor Cecílio Oliveira Gomes; Thatiane Maria Almeida Silveira Mendes (Estudos de Psicologia (Campinas))
Abstract Objective Our objective was to analyze the scientific production of Environmental Psychology in Brazil. Method We conducted a bibliometric documentary research, focusing on articles published by Brazilian authors in open access Latin American journals. Using the descriptor environmental psychology, in the RedALYC, SciELO and PEPSIC databases. Results We identified 160 publications that met the inclusion criteria, published between the years 1997 and 2021. Evidence indicates that national production and communication of scientific knowledge in the area have been carried out with national partnerships, written mostly in the Portuguese language and published in Brazilian journals. Conclusion Finally, we found that empirical research has frequently incorporated qualitative or mixed approaches, as well as an emerging interest in investigations close to the human-environmental experiences of groups with specific characteristics, such as traditional peoples and in rural contexts, representative of the Brazilian and Latin American realities.